Building drought resilience: How Ethiopia’s SPIR Program protects women and families (AMH SUB) - CGIAR; Leight, Jessica; Tambet, Heleene (CGIAR System Organization, 2024)
Climate change is accelerating drought shocks and deepening gender disparities. In Ethiopia, researchers from the CGIAR Initiative on Gender Equality (HER+) partnered with World Vision, CARE, and ORDA Ethiopia to assess whether SPIR, a social protection program with livelihood and nutrition components, helped poor rural women and their households cope with droughts. The study found that drought shocks during the study period led to worse outcomes in food security, assets and domestic violence for non-participants, but that participants in the SPIR program were mostly protected against drought effects on food security and assets and were fully protected against the increase in domestic violence. The study highlights the potential of integrated social protection strategies to safeguard poor rural women and households against adverse impacts of climate change.